The Impact Of The Expansion Of Gunung Rinjani National Park On Land Conflicts And Food Self-Sufficiency Of Local Communities - Royal Sembahulun; Iwan Permadi; Ahmad Imron Rozuli (UNIVERSITAS PAKUAN, 2026)
This study examines the impacts of the expansion of Mount Rinjani National Park (TNGR) on land conflicts and local food self-sufficiency among communities living in surrounding buffer zones in Lombok Island, Indonesia. The expansion of conservation areas and the redefinition of zoning regulations have altered local land tenure systems, restricted access to productive and subsistence land, and intensified conflicts between conservation authorities and local communities, particularly smallholder farmers and indigenous groups. This research employs a qualitative case study approach, using in-depth interviews, field observations, and document analysis involving community members, customary leaders, TNGR officials, local government representatives, and civil society organizations. The findings reveal that land conflicts manifest in multiple forms, including tenurial disputes, horizontal social conflicts, ecological access conflicts, and economic competition related to tourism development. These conflicts have significantly reduced household food production capacity, weakened food diversification, and increased dependence on market-based food systems, thereby undermining local food self-sufficiency. From a political ecology perspective, the study shows that conservation expansion operates as a form of spatial control that reinforces power asymmetries and marginalizes customary land-use systems. The study concludes that effective conflict resolution requires an integrated governance approach that combines formal legal mechanisms with recognition of customary tenure through participatory and collaborative management. Strengthening conservation partnerships, inclusive dialogue, and equitable benefit-sharing mechanisms is essential to reconcile ecological conservation objectives with sustainable livelihoods and long-term food sovereignty of local communities.